Sarcopenia em idosos socialmente ativos : prevalência e relação com as concentrações séricas de ácidos graxos poli-insaturados e marcadores inflamatórios - Margutti, Karen Mello de Mattos (2017)
Sarcopenia is defined as the presence of low muscle mass associated with low muscle strength and/or low physical performance. The outset and evolution of sarcopenia is marked by Inflammation. Studies have shown that supplementation with polyunsaturated fatty acids (PUFAs) may modulate the inflammatory response, thereby aiding protein synthesis and muscle anabolism. Four articles are presented in this thesis, one a systematic literature review and three original articles (cross-sectional design, involving 400 elderly participants of community social groups). The first article, INFLAMMATORY MARKERS, SARCOPENIA AND ITS DIAGNOSTIC CRITERIA IN THE ELDERLY: A SYSTEMATIC REVIEW, sought to understand the relationship between inflammatory markers and sarcopenia and their diagnostic criteria in the elderly. Four of the 154 pre-selected articles were included. An association was found between the inflammatory markers only and the diagnostic criteria of sarcopenia. The second article, SARCOPENIA AND ITS DIAGNOSTIC CRITERIA IN THE ELDERLY: DESCRIPTION OF FREQUENCY AND ASSOCIATION WITH GENDER, AGE, NUTRITIONAL STATUS AND LEVEL OF PHYSICAL ACTIVITY, described the frequency of sarcopenia and its diagnostic criteria, and analyzed its association with gender, age, nutritional status and level of physical activity. The prevalence of sarcopenia was 27.8%, found more frequently in men (50.0%-P<0.001) and those ≥80 years (46.3%-P=0.005). Low muscle mass was more common in men, while low muscle strength and low physical performance were more frequent in the elderly ≥80 years. No association was found between sarcopenia and its diagnostic criteria with nutritional status and level of physical activity. The third article, POLYUNSATURATED FATTY ACIDS IN THE COMMUNITY ELDERLY: DESCRIPTION OF SERUM CONCENTRATIONS AND DIETARY INTAKE, AND ASSOCIATION WITH SARCOPENIA AND ITS DIAGNOSTIC CRITERIA, detailed the serum concentrations and dietary intake of PUFAs, and analyzed their association with sarcopenia and its diagnostic criteria. Serum PUFA concentrations were not associated with sarcopenia. Higher concentrations of dihomo-gamma-linolenic and adrenal acids were associated with low muscle strength and low physical performance, respectively. A lower consumption of PUFA was observed in relation to the recommended and lower omega 6/omega 3 ratio among people with sarcopenia. No association was found between PUFA consumption and diagnostic criteria. The fourth article, INFLAMMATORY BIOMARKERS, SARCOPENIA AND ITS DIAGNOSTIC CRITERIA IN THE SOCIALLY ACTIVE ELDERLY, described the serum concentrations of inflammatory markers and evaluated their association with sarcopenia and its diagnostic criteria. Sarcopenia was associated with lower concentrations of adiponectina. Low muscle mass and low muscle strength were associated with lower adiponectin concentrations and higher hs-CRP, respectively. Low physical performance was associated with lower concentrations of IL-10 and adiponectin, and higher concentrations of IL-6 and TNF-α. Women and the overweight elderly with sarcopenia presented lower concentrations of adiponectin. In conclusion, a high prevalence of sarcopenia was observed in the socially active elderly. The lower food intake of PUFA highlights the need for nutritional interventions. The relationship between sarcopenia and its diagnostic criteria with serum polyunsaturated fatty acid concentrations and inflammatory markers indicates the need to develop new research in order to clarify the mechanisms involved. Further studies are suggested to advance the investigation of PUFA and inflammatory marker interactions in sarcopenia.